Fecal hemoglobin concentration as a measure of risk to tailor colorectal cancer screening: are we there yet?. Issue 4 (July 2015) - Garcia, Montse; Milà, Núria; Binefa, Gemma; Benito, Llúcia; Gonzalo, Núria; Moreno, Víctor
Abstract : The aim of this paper was to examine the distribution of fecal hemoglobin (f-Hb) concentration in a Spanish colorectal cancer screening population according to sociodemographic characteristics and analyze whether f-Hb was associated with clinical outcomes (type of lesion and its location). From September 2009 to November 2012, we sent 77 744 invitations to individuals aged 50–69 years to provide one sample of feces. f-Hb was measured on samples from 27 606 screenees (35.5%). Colonoscopy findings and pathology data were collected on the 1406 screenees with f-Hb greater than 100 ng Hb/ml (20 mg Hb/g feces). The Mann–Whitney U -test and the Kruskal–Wallis test were used to compare f-Hb (median) according to sociodemographic variables, clinical outcomes, and histological features of adenomas. f-Hb from greater than 100 ng Hb/ml was categorized into quartiles. Regression models were used to determine whether f-Hb was a risk predictor of colorectal lesions. f-Hb was associated directly with the severity of the colorectal lesions. An overlap between individuals with a negative colonoscopy and those with a low-risk adenoma was observed. High-grade dysplasia, villous histology, distal location, and increasing size were all features associated with an increased f-Hb level. f-Hb could be used in individual risk assessment to determine surveillance strategies for colorectal cancer screening.